2023
DOI: 10.1186/s12915-023-01712-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of the autism-related SHANK proteins in the human brain

Sarah Woelfle,
Maria T. Pedro,
Jan Wagner
et al.

Abstract: Background SHANKs are major scaffolding proteins at postsynaptic densities (PSDs) in the central nervous system. Mutations in all three family members have been associated with neurodevelopmental disorders such as autism spectrum disorders (ASDs). Despite the pathophysiological importance of SHANK2 and SHANK3 mutations in humans, research on the expression of these proteins is mostly based on rodent model organisms. Results In the present study, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…SHANK3 plays a fundamental role during cerebral development and is highly expressed early during the postnatal course and lifelong for network function; it is a known regulator of the formation and maturation of dendritic spines and integral to synaptic plasticity ( 53 , 73 ). Although systematic regional abundance of SHANK3 in the human brain has not been evaluated, a recent study has identified high levels of expression of the protein in the cortex, hippocampus, and cerebellum in mouse, with expression predominantly in neuronal layers associated with excitatory neurotransmission ( 87 ). Furthermore, white matter evaluations reveal aberrant connectivity in the prefrontal cortex in areas associated with social and cognitive function in both humans and pre-clinical models ( 88 , 89 ).…”
Section: Phelan Mcdermid Syndrome 22q13 Deletion and Other ...mentioning
confidence: 99%
“…SHANK3 plays a fundamental role during cerebral development and is highly expressed early during the postnatal course and lifelong for network function; it is a known regulator of the formation and maturation of dendritic spines and integral to synaptic plasticity ( 53 , 73 ). Although systematic regional abundance of SHANK3 in the human brain has not been evaluated, a recent study has identified high levels of expression of the protein in the cortex, hippocampus, and cerebellum in mouse, with expression predominantly in neuronal layers associated with excitatory neurotransmission ( 87 ). Furthermore, white matter evaluations reveal aberrant connectivity in the prefrontal cortex in areas associated with social and cognitive function in both humans and pre-clinical models ( 88 , 89 ).…”
Section: Phelan Mcdermid Syndrome 22q13 Deletion and Other ...mentioning
confidence: 99%